Who was Galileo? - Demuth, Patricia (Who was-- ?, 2015)
"Like Michelangelo, Galileo is another Renaissance great known just by his first name--a name that is synonymous with scientific achievement. Born in Pisa, Italy, in the sixteenth century, Galileo contributed to the era's great rebirth of knowledge. He invented a telescope to observe the heavens. From there, not even the sky was the limit! He turned long-held notions about the universe topsy turvy with his support of a sun-centric solar system. Patricia Brennan Demuth offers a sympathetic portrait of a brilliant man who lived in a time when speaking scientific truth to those in power was still a dangerous proposition"--